Improving patient recruitment to randomised trials can be cost-effective: A case-study of dexamethasone from the RECOVERY trial - Athanasios Gkekas; Sarah J. Ronaldson; Adwoa Parker; David J. Torgerson (PLoS ONE, 2025)
Background The RECOVERY trial assessed the effectiveness of treatments on preventing severe outcomes from COVID-19 disease in hospitalised patients from 176 NHS hospitals. Clinical benefits of Dexamethasone were observed for hospitalised COVID-19 patients. About 15% of all eligible patients were recruited into the trial. Had patient recruitment been higher the study would have been completed more rapidly. Aim To estimate the cost-effectiveness of improving recruitment to the RECOVERY trial from 15% to 50%, by employing or redeploying two research nurses to each hospital participating in the RECOVERY trial. The analysis is restricted to the evaluation of Dexamethasone versus No Dexamethasone. Methods A decision tree model was developed to estimate the cost-effectiveness of Dexamethasone, against No Dexamethasone. Probability, utility, and cost inputs were used for each pathway and treatment. Then, a cost-utility analysis of clinical practice post-RECOVERY trial (83% Dexamethasone, 17% No Dexamethasone) versus previous clinical practice (100% No Dexamethasone) was undertaken; this analysis was aggregated at the population level and the cost of employing or redeploying two research nurses at each hospital was added, to estimate the cost-effectiveness of faster recruitment to the RECOVERY trial. Results Faster recruitment to the RECOVERY trial could have generated an incremental net benefit of £13,955,476 related to the evaluation of Dexamethasone against No Dexamethasone, thus highlighting the magnitude of the foregone incremental net benefit due to not adopting a more cost-effective clinical practice (83% Dexamethasone, 17% No Dexamethasone) earlier. The findings remain robust following variations in the model’s parameters, with a 85% and 94% probability of faster recruitment being cost-effective given a cost-effectiveness threshold of £20,000 and £30,000 per Quality Adjusted Life Year respectively. Conclusion Slow recruitment to randomised trials can have huge implications for healthcare systems as a result of not introducing a more cost-effective treatment earlier through faster patient recruitment.